REMOVAL OF HEAVY METALS BY ADSORBENT PRODUCED FROM KHAYA SENEGALENSIS - Alhaji Adamu, Yahaya (FUDMA Journal of Sciences, 2023)
Mankind quest for better life has led to advancements in modern technologies which include a number of manufacturing processes and methodologies. Some of these processes and methodologies often release harmful substances into the environment including heavy metals which lead to pollution. These heavy metals are non-biodegradable and therefore need to be removed. Attention has been devoted to emerging technologies which are relatively cheap, for the removal of heavy metal ions from contaminated waters. Adsorption of heavy metal ions using biological materials is one such technologies. As such, the adsorption of Cr(vi), Cd (ii), Zn (ii) and Ni(ii) from synthetic solution by activated carbon from Khaya senegalensis was studied in a batch experiment as a function of pH, metal concentration, adsorbent dose and contact time. Solutions after the batch experiments were analyzed using atomic absorption spectrophotometer. The result revealed dependency of adsorption process on pH. The optimal metal removal occurred at pH 6 for Cd (ii), Zn (ii) and Ni (ii) and 3 for Cr (vi). Maximum adsorption of 82.2 %, 78.9 %, 87.2 % and 83.3 % was attained for Cr (vi), Cd (ii), Zn (ii) and Ni (ii) respectively. Adsorption capacity of the adsorbent improved with initial metal concentration. Ion exchange seemed to be the major mechanism of adsorption in this study. The data collected was were modelled by the Langmuir isotherm over the entire concentration range, suggesting a monolayer coverage. The result showed that, sulphurised Khaya senegalensis is effective in removing heavy metal ions from aqueous solution.
Keywords: Khaya senegalesis; batch experiment; heavy metal; adsorption; efficiency